2010
DOI: 10.1134/s1070428010060138
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aldose condensation products with 2-hydroxyand 2-sulfanylbenzohydrazides

Abstract: The structure of the condensation products of 2-hydroxy-and 2-sulfanylbenzohydrazides with a series of aldoses (L-arabinose, D-ribose, L-ramnose, D-galactose, D-glucose, D-mannose) was studied by 1 H and 13 C NMR spectroscopy. The condensation products of monosaccharides with 2-hydroxybenzohydrazide in DMSO-d 6 solution exist as equilibrium mixtures of linear hydrazone and cyclic pyranose and furanose forms, the cyclic tautomers being represented by two stereoisomers (α-and β-anomers). The aldose condensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, the structure of the compounds under study in the crystalline state was confirmed by solid-phase high-resolution 13 C-NMR spectroscopy (CPMAS). For example, pyranose form B was expected to give a signal from the anomeric C-1 atom at δ 85 -90 ppm; analogous signal from five-membered furanose tautomer C is located at δ 95 -100 ppm [6] [7]. The C-1 signal of possible benzo-1,2,4-triazepin tautomer D should appear in a stronger field, at δ 70-75 ppm, which is typical of sp 3 -hybridized carbon atom in seven-membered ring, located between two nitrogen atoms [4] [5].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the structure of the compounds under study in the crystalline state was confirmed by solid-phase high-resolution 13 C-NMR spectroscopy (CPMAS). For example, pyranose form B was expected to give a signal from the anomeric C-1 atom at δ 85 -90 ppm; analogous signal from five-membered furanose tautomer C is located at δ 95 -100 ppm [6] [7]. The C-1 signal of possible benzo-1,2,4-triazepin tautomer D should appear in a stronger field, at δ 70-75 ppm, which is typical of sp 3 -hybridized carbon atom in seven-membered ring, located between two nitrogen atoms [4] [5].…”
Section: Resultsmentioning
confidence: 99%
“…To a solution of 0.01 mol of SH-containing hydrazide in 25 ml of methanol 0.01 mol of an appropriate aldose was added, and the mixture was boiled for a period of 1-3 h. The solvent was removed at a reduced pressure, and the residue was washed with ether (3 × 50 ml), and the colorless crystalline substance was filtered off on a glass filter funnel (40 -100 μm), dried and stored in a desiccator over P Spectral characteristics of compounds 1b-1e, 2b-2f, 3b-2f, and 4b-4f were described previously [9]- [12].…”
Section: Synthesis Of Aldoses Sh-acylhydrazones (1-4)mentioning
confidence: 99%